Posttransplant Hyponatremia Predicts Graft Failure and Mortality in Kidney Transplantation Recipients: A Multicenter Cohort Study in Korea. - Seung Seok Han; Miyeun Han; Jae Yoon Park; Jung Nam An; Seokwoo Park; Su-Kil Park; Duck-Jong Han; Ki Young Na; Yun Kyu Oh; Chun Soo Lim; Yon Su Kim; Young Hoon Kim; et al. (PLoS ONE, 2016)
Although hyponatremia is related to poorer outcomes in several clinical settings, its significance remains unresolved in kidney transplantation. Data on 1,786 patients who received kidney transplantations between January 2000 and December 2011 were analyzed. The patients were divided into two groups according to the corrected sodium values for serum glucose 3 months after their transplantations (<135 mmol/L vs. ≥135 mmol/L). Subsequently, the hazard ratios (HRs) for biopsy-proven acute rejection, graft failure, and all-cause mortality were calculated after adjustments for several immunological and non-immunological covariates. 4.0% of patients had hyponatremia. Patients with hyponatremia had higher risks for graft failure and all-cause mortality than did the counterpart normonatremia group; the adjusted HRs for graft failure and mortality were 3.21 (1.47-6.99) and 3.03 (1.21-7.54), respectively. These relationships remained consistent irrespective of heart function. However, hyponatremia was not associated with the risk of acute rejection. The present study addressed the association between hyponatremia and graft and patient outcomes in kidney transplant recipients. Based on the study results, our recommendation is to monitor serum sodium levels after kidney transplantations.